Epidemiological Pattern of COVID-19 Infection from March to November 2020 in Situbondo District, East Java, Indonesia - Gesmalah, Mohmed; Hidajah, Atik Choirul (Kesmas, 2021)
The COVID-19 pandemic continues to pose a global threat. As of March 31, 2020, there were 1,528 confirmed COVID-19 cases with 136 deaths in Indonesia. This study aimed to describe the epidemiological features and clinical course of COVID-19 in Situbondo District, East Java Province, Indonesia, to facilitate understanding of the epidemiological situation and the spread of infection in the community to improve the control and prevention measures. This study examined the epidemiological features of COVID-19 cases in Situbondo using descriptive analysis. The results revealed that from March to November 2020, there were 1,622 suspected cases and 816 confirmed cases. Moreover, females (total case 470%) were more likely to be infected than males (total case 346%). Mainly, the cases of COVID-19 infection were in the age group of 19-37 years old (36.8%), and almost half of the confirmed cases (41 cases) were caused by the infection from close contact to confirmed cases, based on the epidemiological investigation report. People with comorbidities were more susceptible to being infected. Hypertension (8.7%), diabetes (8.6%), heart disease (3.7%), kidney failure, and COPD, each by (1%) were the highestreported comorbidities in COVID-19 patients. There was another disease with a low percentage like asthma, pulmonary TB, and cancer. This study opens the gate to further studies, which are needed to understand more about the epidemiological COVID-19 situation in the community.